The assessment of heart rate recovery index in patients with essential tremor - Altuntas, Emine; Cuglan, Bilal; Ozkalayci, Sebnem Karacay (Annals of Medical Research, 2021)
Aim: In this study, it was aimed to investigate whether heart rate recovery index(HRRI), which is marker of cardiovascular mortality, was affected in patients with essential tremor(ET). Materials and Method: The study was conducted as retrospective and it consisted of 30 patients with ET and 30 healthy controls which were similar in terms of age and gender. During admission blood pressure and heart rate, fasting blood tests, hemogram, transthoracic echocardiography and exercise stress test results were recorded. Results: The groups were similar in point of age, gender, smoking(p>0.05). Diastolic and systolic blood pressure of the groups were similar, whereas patients with ET had higher heart rate during admission. When exercise stress test results were assessed, 1 st minute heart rate recovery, 2 nd minute HRRI, 5 th minute HRRI were lower in ET group and these differences were statistically significant(respectively p=0.017; 0.033; 0.019). However both groups were similiar with regards to 3 rd minute HRRI(p=0.063) Conclusion: According to this study results it might be thought that cardiovascular and total mortality may be higher in ET patients than healthy controls due to lower HRRI. Furthermore, it can be speculated that this disease may have an autonomous component since HRRI might be marker of an abnormal autonomic nervous system response.